Isolated primary chylopericardium - (:unkn) unknown (ELSEVIER SCIENCE BV, 1997)
Isolated primary chylopericardum is known to be a rare clinical entity. A 17-year-old girl was diagnosed as isolated primary chylopericardium. She was unresponsive to conservative treatment with pericardial tube drainage and medium chain triglyceride diet. At 2 weeks after the conservative treatment, ligation and resection of the thoracic duct with establishment of a pericardial window through a left thoracotomy was performed. At 6 months, follow-up showed no accumulation of the pericardial fluid. This case also supports that ligation and resection of the thoracic duct with establishment of a pericardial window is the treatment of choice in isolated primary chylopericardium. (C) 1997 Elsevier Science B.V.
Keywords: chylopericardium; primary